INTERNALISASI NILAI PENDIDIKAN KARAKTER DAN SPIRITUAL MELALUI TRADISI PEMBACAAN HIZIB SHOGHIR DI PONDOK PESANTREN AT-TAQWA PUSAT KH. NOER ALIE BEKASI (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
This study is motivated by the limited Living Qur’an research that specifically examines the practice of ḥizb ṣagīr recitation as a manifestation of Qur’anic values within the pesantren tradition. Previous studies on the Living Qur’an have largely focused on the ritual recitation of particular verses, overlooking the educational and social roles of ḥizb practices in shaping students’ character. Therefore, this research aims to analyze the meaning and function of the ḥizb ṣagīr recitation at the At-Taqwa Islamic Boarding School of KH. Noer Alie, Bekasi, and to explore its influence on developing students’ sense of responsibility, discipline, and religious awareness, which ultimately contributes to the institutional stability of the pesantren. Employing a qualitative approach with a descriptive-phenomenological method, data were obtained through observation, in-depth interviews, and documentation. The findings indicate that the ḥizb ṣagīr recitation serves not only as a spiritual practice but also as an educational tool fostering moral discipline, responsibility, and social solidarity among students. This tradition creates a conducive environment for the internalization of Qur’anic values, reinforces the ta‘dẓīm (respectful) relationship between students and teachers, and nurtures a pesantren atmosphere of tranquility, authority, and harmony. Thus, the recitation of ḥizb ṣagīr plays an integral educational role that unites spiritual, moral, and social dimensions, serving as a foundation for character formation and the preservation of Qur’anic values within the pesantren educational system